Angle and Polarization Selective Spontaneous Emission in Dye‐Doped Metal/Insulator/Metal Nanocavities. Issue 1 (20th November 2019) - Caligiuri, Vincenzo; Biffi, Giulia; Palei, Milan; Martín‐García, Beatriz; Pothuraju, Renuka Devi; Bretonnière, Yann; Krahne, Roman
Abstract: Directing and polarizing the emission of a fluorophore is of fundamental importance in the perspective of novel photonic sources based on emerging nanoemitter technologies. These two tasks are usually accomplished by a sophisticated and demanding structuring of the optical environment in which the emitter is immersed, or by nontrivial chemical engineering of its geometry and/or band structure. Here, the wavelength and polarization selective spontaneous emission from a dye‐embedded in a metal/insulator/metal (d‐MIM) nanocavity is demonstrated. A push–pull chromophore with large Stokes shift is embedded in a MIM cavity whose resonances are tuned with the spectral emission band of the chromophore. Angular and polarization resolved spectroscopy experiments reveal that the radiated field is reshaped according to the angular dispersion of the nanocavity, and that its spectrum manifests two bands with different polarization corresponding to the p‐ and s‐polarized resonances of the cavity. The d‐MIM cavities are a highly versatile system for polarization and wavelength division multiplexing applications at the nanoscale, as well as for near‐field focused emission and nanolenses. Abstract : A film of push–pull chromophores is embedded in the dielectric layer of a metal/insulator/metal photonic cavity. The broad‐band emission of this organic fluorophores is modulated by the modes of the photonic cavity, demonstrating angle dependent p‐ and s‐polarized modes. Such ultrathin light‐emitting cavities are highly appealing for integrated optical devices and waveguiding.